Simulating fire sales in a system of banks and asset managers - Susanna Calimani; Grzegorz Halaj; Dawid Żochowski (European Central Bank (ECB), 2020)
We develop an agent-based model of traditional banks and asset managers to investigate the contagion risk related to fire sales and balance sheet interactions. We take a structural approach to the price formation in fire sales as in Bluhm et al. (2014) and introduce a market clearing mechanism with endogenous formation of asset prices. We find that, first, banks which are active in both the interbank and securities markets may channel financial distress between the two markets. Second, while higher bank capital requirements decrease default risk and funding costs, they make it also more profitable to invest into less-liquid assets financed by interbank borrowing. Third, asset managers absorb small liquidity shocks, but they exacerbate contagion when their voluntary liquid buffers are fully utilised. Fourth, a system with larger and more interconnected agents is more prone to contagion risk stemming from funding shocks.
Keywords: C6; G21; G23; 330; fire sales; contagion; systemic risk; asset managers; agent-based model